Development of apricot (Prunus armeniaca L.) powder and its food application - Ahmed, Anwaar; Raza, Ali; Khalid, Naeem; Malik, Arshad Mahmood; Asghar, Muhammad; Abid, Hafiz Muhammad Rizwan (Journal of Pure and Applied Agriculture, 2023)
: Apricot (Prunus armeniaca L.) is a delicious fruit grown in Pakistan. It is known as temperate gold in the northern areas of Pakistan. Apricot is rich in nutrients like vitamins, minerals, phytochemicals, antioxidants, carotenoids and xanthophylls but the fruit is highly perishable and has a short shelf life. This study was carried out to study the acceptability of apricot powder as a functional instant drink and to determine the effect of dehydration on the physicochemical properties of the apricot powder. Apricots were dried in a cabinet dryer to produce their powder that afterward was utilized in the formulation of a drink. The apricot powder was stored for 45 days with 0, 15, 30 and 45 days intervals for its shelf life study. The dehydrated apricots powder was subjected to different physical and chemical analysis e.g. moisture, ash, fiber, bulk density, rehydration capacity, organic acid, antioxidant activity and total phenolic compounds. The results revealed that the moisture content ranged from 3.38 to 7.35 and the bulk density of the powder was increased from 34.37 to 46.88 during the storage, while the rehydration capacity decreased from 4.38 to 3.98 and the ascorbic acid contents decreased from 6.52 to 2.02 mg/100g gradually from 0 to 45 days of storage. Total phenolic contents decreased from 109.91 to 64.53 mg/100g GAE (Gallic Acid Equivalent) and the antioxidant activity of the powder was also decreased from 65.83 to 28.54% during the storage of 45 days at ambient temperature. Sensory characteristics of apricot powder drink depicted acceptable scores for color, taste, flavor and mouthfeel attributes. This study concludes that the apricot powder with a long shelf life is quite suitable for the development of instant drink to harvest functional and nutraceutical benefits of apricot and to decrease economic losses. © 2020 Department of Agricultural Sciences, AIOU